Euro adoption in new EU countries - Ashirov, Iusif; Šíma, Ondřej; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
This thesis deals with the adoption of the Euro in new European countries. Due to the fact that I live and study in the Czech Republic, this country was chosen as the case study. Another country that was selected for the analysis is the Slovak Republic, which is very similar to the Czech Republic in its historical development and economic assumptions, as well as foreign trade. The aim of the thesis is to compare two selected countries - the Czech Republic and Slovakia in the context of economic development after 2009, i.e. after the accession of Slovakia to the Monetary Union. In the Czech Republic, the question of accepting the euro is still hypothetical. It is necessary to understand whether the Czech Republic fulfills the criteria of convergence, including nominal and real convergence, and what are the real reasons for not joining the Czech Republic to the monetary union.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses